The Influence Of Service Quality On Customer Loyalty At PLN Icon Plus Iconnet - Syamsudin, Rifqi Faizurrahman; Pradana, Mahir (eProceedings of Management, 2025)
This study examines the connection between PLN Icon Plus Iconnet's customer loyalty and service quality,highlighting the importance of service quality in building client loyalty. Data was gathered via a Google Form surveythat was directed at 100 PLN Iconnet customers as part of a quantitative approach. The study finds a strong correlationbetween customer loyalty and service quality using Partial Least Squares Structural Equation Modeling (PLS-SEM).Supported by strong reliability and validity measurements in the models, the study emphasizes how crucial it is toprovide high-quality service in order to establish and maintain loyalty. The results offer practical advice for businesseslooking to increase client loyalty and retention through higher-quality services. Keywords -Service Quality, Customer Loyalty, Consumer Behavior, and Customer Satisfaction